Influences of different fuel kinds and engine design parameters on the performance characteristics and NO formation of a spark ignition (SI) engine - Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
This study reports the effects of different fuel kinds such as petroleum based liquid fuels (gasoline, benzene, hexane, iso-octane and toluene), petroleum based gaseous fuels (propane, methane and hydrogen) and alcohols (ethanol and methanol) and engine design parameters such as cylinder dimension, intake pressure and temperature, cylinder wall temperature, residual gas fraction, burning duration, spark timing, equivalence ratio and compression ratio on the engine performance and NO formation of a spark ignition (SI) engine fueled with various fuels. A verified combustion model with experimental studies has been used to understand the influences of engine design parameters and different fuel types on the engine performance and NO formation. The results showed that the engine design parameters and fuel type considerably affect the brake power (BP), brake thermal efficiency (BTE) and NO formation. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Engine performance; Fuel types; NO emission; Combustion; Spark ignition engine; INJECTED DIESEL-ENGINE; LAMINAR BURNING VELOCITY; STEAM INJECTION; EMISSION CHARACTERISTICS; COMBUSTION PROCESS; GASOLINE BLENDS; MILLER CYCLE; OXIDATION CHARACTERISTICS; EXPLOSION CHARACTERISTICS; EXHAUST EMISSIONS; Thermodynamics; Energy & Fuels; Engineering; Mechanics